2012
DOI: 10.1016/j.bbamem.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Folding and stability of membrane transport proteins in vitro

Abstract: Transmembrane transporters are responsible for maintaining a correct internal cellular environment. The inherent flexibility of transporters together with their hydrophobic environment means that they are challenging to study in vitro, but recently significant progress been made. This review will focus on in vitro stability and folding studies of transmembrane alpha helical transporters, including reversible folding systems and thermal denaturation. The successful re-assembly of a small number of ATP binding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 91 publications
0
46
0
Order By: Relevance
“…In an elegant study (34), Bowie and coworkers found that the contribution of eight hydrogen bonds to the stability of Bacteriorhodopsin range from 0.2 to 1.8 kcal∕mol with an average of 0.6 kcal∕mol. While this study suggests that polar interactions are not always highly optimized in membrane proteins, Bacteriorhodopsin is a relatively stable prokaryotic membrane protein (49), for which substantial conformational changes upon function have not been consistently observed (50), and the targeted residues were conserved and functionally important. In our study, we instead sought to uncover general determinants governing the conformational regulation of eukaryotic membrane receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In an elegant study (34), Bowie and coworkers found that the contribution of eight hydrogen bonds to the stability of Bacteriorhodopsin range from 0.2 to 1.8 kcal∕mol with an average of 0.6 kcal∕mol. While this study suggests that polar interactions are not always highly optimized in membrane proteins, Bacteriorhodopsin is a relatively stable prokaryotic membrane protein (49), for which substantial conformational changes upon function have not been consistently observed (50), and the targeted residues were conserved and functionally important. In our study, we instead sought to uncover general determinants governing the conformational regulation of eukaryotic membrane receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Unfolding would start at the ␤-sheet-rich extracellular domain where the ligandbinding site is located (3,69), with a subsequent onset of aggregation when the extent of unfolding proceeds toward the ␣-helical membrane domain. It should be noted that even at 80°C protein unfolding is not complete, as 80% of the ␣-helices are still intact; a similar trend is often observed during thermal unfolding of helical membrane proteins (14,20). A recent study showed this exceptional thermostability by using a helical polyleucine peptide inserted into synthetic lipid vesicles.…”
Section: -Ht 3 R Increases Conformationalmentioning
confidence: 97%
“…Alternatively, MPs can accumulate in large amounts in inclusion bodies without killing the host cell, but they do not fold properly and are recovered under a denatured form. Folding them to their native state is a highly challenging endeavor, protein-specific, very time-consuming to develop, and plagued with low folding yields (for recent general reviews about in vitro folding of MPs, see e.g., Buchanan et al 2012; Harris and Booth 2012; Otzen and Andersen 2013; Popot 2014). …”
Section: Applicationsmentioning
confidence: 99%